Елітарність і загальносприйнятність поетичної мови Ліни Костенко - Сюта, Г. (Культура слова, 2020)
У статті продемостровано феномен елітарності та
загальносприйнятності поетичної мови Ліни Костенко –
унікального явища сучасної української лінгвокультури. Доведено,
що гармонію елітарності й загальносприйнятності творять три
естетично-креативні виміри: світове, національне й індивідуальне.
Ментально мовотворчість Л. Костенко сформована на досвіді
світової та національної культури, а вербалізація цього досвіду
відбувається в переломленні через індивідуальне світобачення
авторки. The article proves that elitism and universality, common accessibility
defining creative and aesthetic features of Lina Kostenko’s poetic language.
Their harmony is created by three aesthetic and creative dimensions:
world, national and individual.
World culture in L. Kostenko’s texts reflects by different lingual-andaesthetic
units – images, aphorized statements, quotations. Panoramic
linguo-culturally holistic perception of world culture in the poetry of Lina
Kostenko represents the dictionary of precedent names. This dictionary
is formed by names from the texts of Bible, culture of antiquity, folklore,
literature, fine arts. Together they form a holistic elitist-intellectual text, the
perception of which presupposes the presence of a prepared, erudite reader.
L. Kostenko’s mini-texts and definitions persuasively reflects the
national worldview. That is why they were organically included to the
dictionary of literary language, enriched the arsenal of means of intellectual
communication as recognizable, emotionally resonant formulas. Today they
are actively used to confirm the opinion in various discourses – in journalism,
in political rhetoric, in educational, in didactic and scientific literature.
One of the factors of elitism just like as of the common accessibility of
L. Kostenko’s poetry is her unique ability to verbalize world and national
experience as her own. This feature unites L. Kostenko’s poetics with the
traditions of T. Shevchenko and, Lesya Ukrainka.
The accessibility of L. Kostenko’s artistic maxims as units of
communication is promoted by knowledge of psychology, mentality of
our contemporaries. They determine the correct formulations of poetic
definitions. Among the most frequently updated – existential concepts
(life, death), moral categories (conscience, truth, truth), feelings (love,
sadness), abstract concepts (irony, vulgarity, glory). Many of them have
already become formulas for verbalization of both collective and personal
intellectual and emotional experience.
Important factor of accessibility of L. Kostenko’s language is its growth
from aesthetics, melody and philosophy of national language. Folk words,
forms, constructions reflect the natural flow of the author’s thinking.
L. Kostenko’s poetic language is an illustrative intellectual-temporal
fragment of Ukrainian literary and artistic language of the second half of
the XX – beginning of the XXI century. It combines the intellectualism
and emotionality, bookishness and deep nationality, national sensuality.